Bibliometric Analysis of Rhizomatic Learning in Educational Research - Judijanto, Loso (Eastasouth Institute, 2025)
This study presents a bibliometric analysis of scholarly literature on rhizomatic learning in educational research, aiming to uncover its intellectual structure, thematic developments, and collaborative patterns. Using data retrieved from the Scopus database (2008–2024) and analyzed with VOSviewer, the study visualizes co-citation networks, keyword co-occurrences, country collaborations, and temporal trends. The findings reveal that rhizomatic learning is conceptually grounded in poststructuralist philosophy, particularly the works of Gilles Deleuze and Félix Guattari, and is increasingly applied in digital pedagogy, professional development, and lifelong learning contexts. Central themes such as connectivism, new materialism, and multiplicity demonstrate the field’s interdisciplinary depth, while emerging topics like sustainability and adult learning reflect its practical expansion. The research also highlights a concentration of scholarly output in Anglophone countries and a predominance of qualitative methodologies. This study contributes to a deeper understanding of rhizomatic learning's evolution and offers a foundation for future inquiry that bridges theory, practice, and global educational needs.